TouchMover: Actuated 3D Touchscreen with Haptic Feedback - Sinclair, Mike; Pahud, Michel; Benko, Hrvoje (Interactive Tabletops and Surfaces (ITS 2013), St Andrews, UK, 2013)
This paper presents the design and development of a novel visual+haptic device that co-locates 3D stereo visualization, direct touch and touch force sensing with a robotically actuated display. Our actuated immersive 3D display, called TouchMover, is capable of providing 1D movement (up to 36cm) and force feedback (up to 230N) in a single dimension, perpendicular to the screen plane. In addition to describing the details of our design, we showcase how TouchMover allows the user to: 1) interact with 3D objects by pushing them on the screen with realistic force feedback, 2) touch and feel the contour of a 3D object, 3) explore and annotate volumetric medical images (e.g., MRI brain scans) and 4) experience different activation forces and stiffness when interacting with common 2D on-screen elements (e.g., buttons). We also contribute the results of an experiment which demonstrates the effectiveness of the haptic output of our device. Our results show that people are capable of disambiguating between 10 different 3D shapes with the same 2D footprint by touching alone and without any visual feedback (85% recognition rate, 12 participants).
ACM ITS 2013 Best Paper Award